Root Canal Morphology of Mandibular Second Molars Using CBCT - Mohamad Qulam Zaki Bin Mohamad Rasidi1, Mahesh Ramakrishnan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: A thorough knowledge of root canal system, anatomy and variation in morphological plays an important role in all scopes of endodontic treatment. The practitioner should have a great understanding of the detailed morphological anatomy of root canal system in order to utilize the proper technique and method during the endodontic treatment especially in mandibular second molar.Aim: To evaluate root canal morphology of mandibular second molars using Cone Beam Computed Tomography (CBCT) in Chennai Population based on Vertucci’s classification.Materials and Method: The CBCT scans of patient age between 20 years to 40 years were retrieved from Department of Oral Medicine and Radiology, Saveetha Dental College, Chennai, India from September 2018 to January 2019. The teeth were observed for the root canals system using Vertucci classification, and other parameters. The comparison between males and female were made.Results: Generally the parameter values are more in females when compared to males and the most prevalence root canal configuration are Type 4, followed by Type 2 in mesial and distal roots for both gender.Conclusion: The study indicates the significant values to certain extendand can serve as aids to utilize the proper technique and method during the endodontic treatment especially in permanent mandibular second molar.